Modelling vacancy microvoid formation in dislocation-free silicon single crystals - Talanin, V.I.; Talanin, I.E.; Koryagin, S.A.; Semikina, M.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
An alternative mathematical model of vacancy microvoid formation in dislocation-free silicon single crystals was represented. The analysis of conditions of microvoid nucleation inside the bulk of crystals during cooling after their growth was carried out. The possibility of formation of a quasi-stationary microvoid profile in large-scale crystals within the temperature range 1130…1070 °С has been shown.